2020
DOI: 10.1016/j.jinf.2020.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Environmental contamination of SARS-CoV-2 in healthcare premises

Abstract: Objectives: A large number of healthcare workers (HCWs) were infected by SARS-CoV-2 during the ongoing outbreak of COVID-19 in Wuhan, China. Hospitals are significant epicenters for the human-to-human transmission of the SARS-CoV-2 for HCWs, patients, and visitors. No data has been reported on the details of hospital environmental contamination status in the epicenter of Wuhan. Methods: We collected 626 surface swabs within the Zhongnan Medical Center in Wuhan in the mist of the COVID-19 outbreak between Febru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
216
3
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(251 citation statements)
references
References 9 publications
16
216
3
16
Order By: Relevance
“…Secondary (indirect) transmission of SARS-CoV-2 through contamination of HITES by droplets and respiratory aerosols or other patient secretions/excretions (bronchoalveolar uid, sputum, mucus, blood, lacrimal uid, semen, urine, and feces) also is thought to occur [24][25][26][27] . The indirect transmission pathway, envisioned as a patient's bodily uids-HITES-hands-mucous membrane nexus, is supported by experimental transmission studies in animal models 28 and by the results of investigations of the contamination of HITES with SARS-CoV-2 RNA in healthcare settings 25,[29][30][31] . The detection of infectious SARS-CoV-2 in patient feces 32,33 , together with the data on survival of SARS-CoV-2 in fecal suspensions 20,21 , suggest that a fecal/oral or fecal/respiratory route of transmission is possible.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary (indirect) transmission of SARS-CoV-2 through contamination of HITES by droplets and respiratory aerosols or other patient secretions/excretions (bronchoalveolar uid, sputum, mucus, blood, lacrimal uid, semen, urine, and feces) also is thought to occur [24][25][26][27] . The indirect transmission pathway, envisioned as a patient's bodily uids-HITES-hands-mucous membrane nexus, is supported by experimental transmission studies in animal models 28 and by the results of investigations of the contamination of HITES with SARS-CoV-2 RNA in healthcare settings 25,[29][30][31] . The detection of infectious SARS-CoV-2 in patient feces 32,33 , together with the data on survival of SARS-CoV-2 in fecal suspensions 20,21 , suggest that a fecal/oral or fecal/respiratory route of transmission is possible.…”
Section: Discussionmentioning
confidence: 99%
“…The facts of COVID-19 human-to-human transmission and SARS-CoV-2 viral RNA being detected on different inanimate surfaces and droplets in air in healthcare and patient's family settings have indicated the virus may be airborne transmission [52] , [55] , [135] , [136] , [137] , [138] . It is widely accepted that the respiratory droplets are the main transmission way when a person has close contact with an infected person [6] , [139] .…”
Section: Characteristics Of Coronaviruses In Aerosol and Inanimate Sumentioning
confidence: 99%
“…Furthermore, the virus RNA in the table, chair, floor, and fan surfaces has been detected in the patient’s room, which may create a condition to transfer virus [154] . A number of studies have shown that coronaviruses could persist (a few hours to days) on inanimate surfaces [10] , [51] , [95] , [135] , [155] .…”
Section: Characteristics Of Coronaviruses In Aerosol and Inanimate Sumentioning
confidence: 99%
“…Desafortunadamente, en este grupo poblacional la inequidad en salud y la exclusión son los desafíos más importantes para la salud pública y el bienestar. Dar prioridad a los mayores de 60 años con la participación de los equipos de salud de la APS es un área de oportunidad que debe aprovecharse durante la pandemia con estrategias de prevención, promoción, información, educación y comunicación de los factores de riesgo de las comorbilidades para evitar contagios y reducir la demanda de servicios curativos en hospitales de segundo y tercer nivel, que tienen un mayor riesgo de contaminación y transmisión con el SARS-CoV-2 ( 44 ).…”
Section: Objetivos De La Raes a Corto Y Mediano Plazosunclassified